RELASHIONSHIP CONFLICTS AT WORK IN PRESCHOOL INSTITUTIONS, THEIR CAUSES - Mirzojanc, Liudoslava Teresa; Survutaitė, Dalia (Acta Paedagogica Vilnensia, 2007)
The leader of preschool institutions has to deal with various conflicts which he/she has to participate in and even exercise the role of mediator between the employees while solving different institutional tasks and controlling relationships at work.The leader of preschool institutions has to deal with various conflicts which he/she has to participate in and even exercise the role of mediator between the employees while solving different institutional tasks and controlling relationships at work.Conflicts, their causes and solutions at work in educational system, beginning with preschool institutions, are not given proper attention, although this problem exists.The aim of present work is to analyze conflicts which rise at work in preschool institutions. Data in the article refer to the works of Lithuanian scientist and foreign countries experience. It is based on a research on labor relations conflicts at the preschool institutions done in Vilnius.The present paper consists of three parts. The first part discusses the notion of relationships conflicts at work, various classifications, functions and causes of the conflicts. The second part focuses on the analysis of how to regulate the conflicts at work, what is the influence of working atmosphere to the problem of conflicts, the specific features of the conflicts and their solutions. What is more, the same part deals with the methods of prevention of those conflicts given by various authors. The third part presents the analysis of relationship conflicts at work.In order to analyze the conflicts at work in preschool institutions, their causes, the research was hold in February-March, 2006. The leaders and some of the employees (teachers and other service personnel) of Vilnius preschool institutions were given anonymous questioners. As the part of the questioners did not return after the first poll, the questioners were given one more time at the meeting of preschool institutions leaders. The number of respondents were 300 (100 were the leaders of Vilnius preschool institutions, 100 teachers of Vilnius preschool institutions and 100 service personnel of Vilnius preschool institutions).The data of the research were processed using Statistical Social Science 12.0 version.The research shows that the conflicts which rise in preschool institutions are very emotional, the highest level of conflicts is typical in the interaction of the leaders and service personnel in preschool institutions, the lowest level of conflicts is typical between the leaders; long and complicated conflicts are rare in preschool institutions. The method of consensus is used by every employee in preschool institutions. The research discloses that the main cause of conflicts in preschool institutions is lack of information and legal knowledge.
Keywords: conflicts in work-relations; preschool educational institution; leaders; pedagogues; operating personnel